The Impact of Implicit-Bias-Oriented Diversity Training on Police Officers’ Beliefs, Motivations, and Actions - Lai, Calvin K.; Lisnek, Jaclyn A. (Psychological Science, 2023)
U.S. police departments have attempted to address racial inequities in policing with diversity training. However, little research has evaluated whether these trainings are effective at changing officers’ beliefs, motivations, and actions. To examine their efficacy, we tested a day-long implicit-bias-oriented diversity training designed to increase U.S. police officers’ knowledge of biases, concerns about bias, and use of evidence-based strategies to mitigate bias (total N = 3,764). The training was immediately effective at increasing knowledge about bias, concerns about bias, and intentions to address bias, relative to baseline. However, the effects were fleeting. Although the training was linked to higher knowledge for at least 1 month, it was ineffective at durably increasing concerns or strategy use. These findings suggest that diversity trainings as they are currently practiced are unlikely to change police behavior. We conclude with theorizing about what organizations and training programs could do for greater impact.